A qualitative exploration of barriers to university students' willingness to attend sexual violence prevention workshops. Issue 2 (4th March 2021) - Graham, Katie; Treharne, Gareth J.; Liebergreen, Nicola; Stojanov, Zoran; Shaw, Rachel; Beres, Melanie A.
ABSTRACT: Universities have implemented a range of education programmes to address the problem of sexual violence on campus. While these programmes can improve the attitudes and behaviours that contribute to rape culture, little is known about the factors influencing students' decisions to participate in such programmes. The aim of this study was to understand university students' decisions about attending sexual violence prevention workshops. Focus groups or individual interviews were conducted with 28 students at a university in Aotearoa/New Zealand who had attended a prevention workshop (n = 11) or who had had the opportunity to attend (n = 17). Thematic analysis was used to analyse the data with a focus on barriers to students' willingness to engage with sexual violence prevention education. Three themes were developed. Each theme concerned preconceived ideas about sexual violence that impacted students' perceptions of and willingness to engage in sexual violence prevention. The three barriers consisted of perceptions concerning the relevance of programmes, participants' perception that they already knew the content, and the impact of cultural ideas about gender and sexual violence. These findings have practical implications for the development and promotion of future campus sexual violence prevention programmes.